Political Religion and Politicized Women in Turkey: Hegemonic Republicanism Revisited - Eslen‐Ziya, Hande (Totalitarian movements and political religions, 2010)
Since its establishment in 1923, the Republic of Turkey has assumed a sacred character, owing primarily to the influence of republicanism, the country’s dominant political religion. Processes of modernization, inherent in republicanism, became the main instigators for the improvement of women’s rights in Turkey from the 1920s and 1930s onwards. However, thanks to the subsequent Europeanization process in Turkey, coinciding with the new millennium, modernization has acquired new meanings. The new interpretations of modernization, do not necessarily support the dominant political religion in Turkey. Gender policy is a crucial area to gauge how modernization and republicanism clash and/or converge with each other. This article comprehensively examines how, very recently, the demands of gender rights activists have accentuated differences between republicanism and modernization. We argue that the schism among womens’ groups in the public sphere regarding rights has been important for triggering debate and questioning the ongoing salience of republicanism. The article contributes to literature on political religions by suggesting that the sacralization of the republic, driven by Turkish nation‐building processes in our case, may be hampered by the process of modernization once this process becomes autonomous from sacralization and generates its own momentum.